Revealing the Role of Service Quality and Brand Awareness in Shaping Customer Satisfaction Mobile Banking Users Through Excellent Service - Wahyu, Wahyu Maulana; Istianah Asas (LPPM Universitas Negeri Jakarta, 2024)
Banking in Indonesia has been actively developing mobile banking-based technology because many already have this facility. Transactional banks in Indonesia, on average, can be said to experience electronic transactions every month, reaching 80-90 percent of the number of customer transactions. The top brand index in mobile banking in this research is trending downward from 2020 to 2022. This is the basis for conducting this research. The research was conducted with a sample of customers who used the mobile banking application and the research was carried out at the Pamekasan Branch KCP. This type of research is quantitative research with secondary data originating from questionnaires. The analysis tool used is SmartPLS with SEM-PLS data analysis techniques. The results of the direct influence research show that the service quality variables (p-value 0.035) and brand awareness (p-value 0.040) have an effect on customer satisfaction, while the service quality variables (p-value 0.278) and brand awareness (p-value 0.216) have no effect on excellent service and excellent service (p-value 0.095) have no effect on customer satisfaction. The indirect influence research results show that excellent service is not an intervening variable between service quality variables (p-value 0.321) and brand awareness (p-value 0.248) on customer satisfaction